Application of the Abbey pain scale for assessment of acute perioperative pain in elderly patients with impaired communication following a femur fracture - Jerleković, Marica (Array, 2020)
Pain resulting from physical trauma and surgical procedures is very strong. In elderly patients, especially those with impaired communication or cognitive damage, it is assessed rarely or not at all. The importance of pain assessment is reflected in quality supervision and adequate treatment which decrease complications and speed up recovery. The aim of the study was to determine the metric characteristics (reliability and validity) of the Abbey Pain Scale on a population of elderly patients with impaired communication in Croatia and to demonstrate the correlation between the assessed acute pain level and analgesia efficacy. The sample consisted of 31 patients above the age of 65 hospitalized after a femur fracture at the Department of Traumatology, Sestre Milosrdnice University hospital, Zagreb, Croatia. The Abbey Pain Scale and Visual Analogue Scale were used for pain assessment. The patients’ mental status was evaluated using Mini-Mental State Examination. The data was processed using Chi-squared and Cronbach’s alpha tests, and small dependent samples were tested using T-test. The value of Cronbach’s alpha coefficient of 0.561 for the Abbey Pain Scale was considered acceptable. The score on the Abbey Pain Scale correlates significantly with the result of a standardized self-assessment of pain intensity (r = 0.739, p= 0.001). We conclude that the Abbey Pain Scale serves as a convenient tool for assessing pain intensity in patients with impaired communication, and its use is indirectly related to satisfactory analgesia, due to good metric characteristics of validity and reliability.